AN ERROR ANALYSIS ON THE USE OF SIMPLE PRESENT TENSE IN STUDENTS’ WRITING DESCRIPTIVE TEXT AT THE EIGHT GRADE OF SMP NEGERI 1 GUNUNGSITOLI SELATAN IN 2020/2021 - Nursayani Maru’ao; Hidayati Daeli; Juni Lestari Lafau (Universitas Nias, 2022)
Simple present tense is one of the tenses is tense denoting an action happening in this time. Moreover, descriptive text is one of text types which uses simple present tense. However, based on the observation, the researcher found that the students make errors in using simple present tense in writing a descriptive text. . Corder in Ellis (1994:48) proposes the steps in error analysis..research, they are Collecting of a sample of learner language, Identification of error, Description of errors, Explanation of error and Evaluation of errors. The purposes of the research to analyze the dominant of errors and the source of the errors made by the eighth grade of SMP Negeri 1 Gunungsitoli Selatan of using simple present tense in writing descriptive text. The researcher was conducted to the 24 eighth grade students of SMP Negeri 1 Gunungsitoli Selatan by using descriptive qualitative method. The data of the research were documentary of the student’s of descriptive text writing and the transcript interview to the students as well as transcript of interview to the English teacher. From the result of the research, it could be seen that the most errors made by students were Omission with the frequency of source was 45 or 49%, Misformation was 34 or 37%, Addition was 13 0r 14% and Misordering was 0 or 0%. Based on the result of the Interviews. It showed that the students error were mostly affected by Intralingual with the frequency of source was 69 or 80%, then followed by Interlingual which was 17 or 20%